Back pain in adolescent athletes - Young, W. K.; d`Hemecourt, P. A. (The Physician and Sportsmedicine, 2011)
Back pain in the young athlete is a common complaint and often perceived as a challenging problem. A well-directed approach will usually provide the practitioner with a higher comfort zone. The etiology of back pain in the pediatric and adolescent population is different from that of the adult population due to the presence of open physes and increased linear growth velocity. In addition, the frequency and intensity of sports participation in children continues to increase, leading to more overuse injuries. This review article will discuss the anatomy and physiology of the spine and pelvis, as well as focus on the chronic and overuse causes of back pain in the young athlete.